Payment by Results - Brendan A. Rapple (Arizona State University, 1994)
Today the public is demanding that it exercise more control over how tax dollars are spent in the educational sphere, with multitudes also canvassing that education become closely aligned to the marketplace's economic forces. In this paper I examine an historical precedent for such demands, i.e. the comprehensive 19th century system of accountability, "Payment by Results," which endured in English and Welsh elementary schools from 1862 until 1897. Particular emphasis is focused on the economic market-driven aspect of the system whereby every pupil was examined annually by an Inspector, the amount of the governmental grant being largely dependent on the answering. I argue that this was a narrow, restrictive system of educational accountability though one totally in keeping with the age's pervasive utilitarian belief in laissez-faire. I conclude by observing that this Victorian system might be suggestive to us today when calls for analogous schemes of educational accountability are shrill.